2008
DOI: 10.1063/1.3029774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and transport property of AgSbTe2 as a promising thermoelectric compound

Abstract: Polycrystalline AgSbTe2 ternary compound materials with high phase purity were fabricated using a combined process of mechanical alloying and spark plasma sintering. It was found that stoichiometric AgSbTe2 is a promising composition for low-and-mediate temperature applications, whose ZT reaches 1.59 at 673K, benefiting from its extremely low thermal conductivity (0.30W∕mK) in addition to its low electrical resistivity (<1.1×10−4Ωm) and large positive Seebeck coefficient (260μV∕K). On the other hand, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 18 publications
7
101
1
2
Order By: Relevance
“…A relaxation-time model for electrical carrier-interface scattering was developed to account for the fi ltering eff ect of low-energy electrons on transport properties. Tl x Pb 1-x Te [17] AgSbTe 2 [14] Ag-Pb-Sb-Te (LAST) [15] (GeTe) 1-x (AgSbTe 2 ) x (TAGS) [16] CsBi 4 Te 6 [12] Yb x Co 4 Sb 12 (skutterudites) [18] SiGe [19] Yb x Ba 8-x Ga 16 Ge 30 (clathrates) [25] Hf 0.6 Zr 0.4 NiSn 0.98 Sb 0.02 (half-Heusler) [24] Yb 14 Mn 1-x Al x Sb 11 (Zintl phase) [23] Temperature ( n-type (Mg 2 Si y Ge 1-y )-(Mg 2 Si 0.6 Ge 0.4 ) nanocomposites. Th e inspired work of Kanatzidis's group revealed that a new kind of intrinsic nano-inclusion, as shown schematically in Figure 3(k), formatted by the segregation of silver and antimony in the lead sublattice of PbTe, could achieve simultaneous phonon blocking and electron transmission.…”
Section: Nanostructural Approaches For Enhancing Thermoelectric Perfomentioning
confidence: 99%
See 3 more Smart Citations
“…A relaxation-time model for electrical carrier-interface scattering was developed to account for the fi ltering eff ect of low-energy electrons on transport properties. Tl x Pb 1-x Te [17] AgSbTe 2 [14] Ag-Pb-Sb-Te (LAST) [15] (GeTe) 1-x (AgSbTe 2 ) x (TAGS) [16] CsBi 4 Te 6 [12] Yb x Co 4 Sb 12 (skutterudites) [18] SiGe [19] Yb x Ba 8-x Ga 16 Ge 30 (clathrates) [25] Hf 0.6 Zr 0.4 NiSn 0.98 Sb 0.02 (half-Heusler) [24] Yb 14 Mn 1-x Al x Sb 11 (Zintl phase) [23] Temperature ( n-type (Mg 2 Si y Ge 1-y )-(Mg 2 Si 0.6 Ge 0.4 ) nanocomposites. Th e inspired work of Kanatzidis's group revealed that a new kind of intrinsic nano-inclusion, as shown schematically in Figure 3(k), formatted by the segregation of silver and antimony in the lead sublattice of PbTe, could achieve simultaneous phonon blocking and electron transmission.…”
Section: Nanostructural Approaches For Enhancing Thermoelectric Perfomentioning
confidence: 99%
“…Th eir microstructural analysis revealed that the high ZT value is partially attributable to a signifi cant decrease in κ lat due to scattering at the grain boundary and the presence of nano-precipitates [49]. Tang et al [14] developed a melt-quench-anneal-spark plasma sintering method to form bulk nanostructural p-type Bi 0.52 Sb 1.48 Te 3 with a ZT value at of 1.56 at 300 K. Cao et al [50] obtained a maximum ZT of 1.47 at ca. 438 K for Bi 2 Te 3 /Sb 2 Te 3 bulk nanocomposites with laminated nanostructures using a simple route involving hydrothermal synthesis and hot pressing.…”
Section: Bi 2 Te 3 -Based Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, high-performance single-phase thermoelectric materials can be obtained using materials with intrinsically low lattice thermal conductivities. Typical materials included in this class are as follows: AgSbTe 2 (kB0.39 Wm À1 K À1 , ZTB1.6 at 673 K), 10,11 Ag 9 TlTe 5 (kB0.22 Wm À1 K À1 , ZTB1.2 at 700 K), 12 Ag 0.95 GaTe 2 (kB0.20 Wm À1 K À1 , ZTB0.7 at 850 K), 13 Ag 3.9 Mo 9 Se 11 (kB0.75 Wm À1 K À1 , ZTB0.6 at 800 K), 14 Cu 3 SbSe 4 (kB0.50 Wm À1 K À1 , ZTB0.8 at 650 K), 15 Cu 2 Ga 4 Te 7 (kB0.67 Wm À1 K À1 , ZTB0.6 at 940 K), 16 Cu 2.1 Zn 0.9 SnSe 4 (kB0.50 Wm À1 K À1 , ZTB0.9 at 860 K), 17 Cu 2 Ga 0.07 Ge 0.93 Se 3 (kB0.67 Wm À1 K À1 , ZTB0.5 at 745 K), 18 CsBi 4 Te 6 (kB0.50 Wm À1 K À1 , ZTB0.8 at 275 K), 19 and K 2 Bi 8 Se 13 (kB0.80 Wm À1 K À1 , ZTB0.4 at 400 K). 20 Recently, we reported a quaternary BiCuSeO compound that exhibits very low thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%